Дослідження інноваційного розвитку промислових підприємств Львівщини - Цогла, О. О. (Видавництво Львівської політехніки, 2015)
Розглянуто та опрацьовано ситуацію щодо інноваційного розвитку підприємств Львівського регіону. Проведено аналіз інноваційного розвитку промислових підприємств Львова та області. Визначено фактори, які впливають на інноваційне становище, що склалося за останні роки в економіці регіону. Підкреслено, що основними чинниками, що гальмують ведення бізнесу в сфері інноваційної діяльності, є нестабільність державної політики, податкова політика і податкові ставки. The innovative development of enterprises in Lviv region is studied and reviewed in the article. The analysis of innovative development of industrial enterprises in Lviv region is done. The factors influencing the innovative situation that has arisen in recent years in the region's economy are identified. The situation that has developed in recent years in Ukraine's economy is determined by the inefficiency of the conducted economic reforms, imperfection of tax system, the negative impact of state regulation on the activities of economic entities. However, fundamental factors of economic growth are resources and innovation. But, as in recent decades the problem of resource provision has aggravated, the current market environment requires the intensification of innovative activity. Competitiveness of Lviv region depends on the ability to introduce innovations, modernize production and technological processes adjusting to changing environmental conditions. However, during the analysis of the innovative activity of Lviv industrial enterprises it was found that innovative measures were taken only by 16.4% of all the industrial companies in the region, and the volumes of sales of innovative products are only 3% of total industrial output. It was revealed that were no financial support for innovation at the expense of foreign investors and the state in 2014; the main source of financing innovations was own funds of enterprises that decreased in recent years; financing from the local budgets is insufficient. In the region, as well as in the whole country, there is no venture financing, that is why the reduction of innovation efficiency is a long-term trend. The limited amount, and sometimes even absence of innovations funding from the state budget, lack of economic incentives to attract investment resources in innovations processes, uncertainty of institutional environment for the development of innovations infrastructure (technology parks, technopolises, technology transfer centers etc.) cause deterioration of the innovations conditions of the regions and encourage independence and self-financing of business activities.
Research into innovative development of industrial enterprises in Lviv region
Keywords: інноваційний розвиток; регіональні особливості; інноваційна активність промислових підприємств; інноваційні витрати; інноваційна продукція; innovative development; regional features; innovative activity of industrial enterprises; innovation costs; innovative products